Do epistemic reasons bear on the ought simpliciter? - Mantel, Susanne (Philosophical issues, 2019)
Are epistemic reasons normative in the same sense as, for instance, moral reasons? In this paper I examine and defend the claim that epistemic reasons are normative only relative to an epistemic standard. Unlike moral reasons they are not substantially normative, because they fail to make an independent contribution to obligations or permissions simpliciter. After presenting what I take to be the main argument for this view, I illustrate that the argument has often been defended by examples which controversially presuppose strong epistemic obligations or pragmatic reasons for belief. Opponents of the argument often deny the existence of obligations and reasons of these kinds. I therefore examine whether the argument can withstand that line of critique by employing new examples.